Double rhomboidal flap for reconstruction of large surgical defect of the labial commissure - Andrade, Pedro (2012)
Closure of perioral surgical defects involving the oral commissures is highly challenging. We describe a 69-year-old male patient with a large basal cell carcinoma of the right perioral region, extending to the right oral commissure. This lesion was radically excised, and the resulting surgical defect was closed using a homolateral double opposing rhomboidal flap. The final result was esthetically very satisfactory, with total preservation of lip function. Double opposing rhomboidal flaps are viable surgical options for the reconstruction of surgical defects involving the perioral area and oral commissures. In this relatively simple procedure, donor skin is obtained from the nearby cheek and mandibular areas, under low risk of surgical complications, preserving lip function without distortion of the labial anatomy.